Bridging the gap between assessment and action: recommendations for the effective use of LCA in the building process. Issue 2 (November 2020) - Beemsterboer, Sjouke; Baumann, Henrikke; Wallbaum, Holger
Abstract: Environmental life cycle assessment (LCA) witnesses increasing popularity in the built environment. LCA stimulates among others an efficient use of natural resources and a reduction of carbon emissions through quantification of material and energy inputs and emissions in the building life cycle. Thereby, LCA aspires to contribute to SDG12 on ensuring sustainable consumption and production patterns. Despite high ambitions, the actual influence of LCA in construction projects is often modest. The mere application of LCA methodology in a building project is insufficient to produce a more environmentally friendly building. To better understand the practical conditions under which an LCA may induce change in a building project, we propose to analyse the use of LCA from a processual perspective. This paper presents a case study of a building product development project in which a processual perspective is applied on LCA. Using a longitudinal ethnographic methodology, key actors are followed through environmentally relevant episodes as the building project matures. A progressive LCA quantifies the potential environmental impact of the project as it progresses through different stages of the building process. Based on the learnings from this study, recommendations are presented to support the effective use of LCA in sustainable building practices, and contribute to SDG12 on sustainable consumption and production patterns.